Cloud Manufacturing framework for controlling and monitoring of machines - Nayyef, Ibrahim Kh. Kh.; Shammari, Ahmed Z. M. (Al-Khwarizmi Engineering Journal, 2020)
Due to the development that occurs in the technologies of information system many techniques was introduced and played important role in the connection between machines and peoples through internet, also it used to control and monitor of machines, these technologies called cloud computing and Internet of Things. With the replacement of computing resources with manufacturing resources cloud computing named converted into cloud manufacturing. In this research cloud computing was used in the field of manufacturing to automate the process of selecting G-Code that Computer Numerical Control machine work it, this process was applied by the using of this machine with Radio Frequency Identification and a AWS Cloud services and some of python libraries such as PAHO to make the connection between devices. Present sensor value (A sensor called DHT sensor used in this research to measure temperature and humidity) on cloud to help operator make decision. This technology was used to eliminate paper work, provide a real time monitoring of machines and give the upper level of management to take their decisions about the products and its status to begin the shipping to the costumer